Istikhdām Lu’bah al-Taghmiyah al-Lughawiyah fi Tarqiyyah Mahārat al-Kalām fī Madrasah al-Munīr al-Ibtidāiyah - Nur, Mujiburrahman; Mursidin, Mursidin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Learning a language is not an easy thing. Various problems still appear often and are almost rarely solved. The problem of teaching Arabic needs special attention. The lack of success in learning Arabic at various school levels is basically influenced by many factors, including factors of learning methods and strategies that are less active, creative and fun so that sometimes students are not enthusiastic in participating in learning. This study aims to first determine the application ofthe al-Taghmiyyah language game in the learning of Mahârat al-kalâm in Madrasah Ibtidaiyah Al-Munir. Second, knowing the advantages and disadvantages of the al-Taghmiyyah language game in learning Mahârat al-kalâm at Madrasah Ibtidaiyah Al-Munir. The research uses qualitative research with data collection techniques using interviews, observations and in-depth interviews. The results of the study show that the application of the At-taghmiyyah language game is adjusted to the lesson plan that has been made by the teacher which consists of several stages starting from the introduction, core and closing activities, the advantage of this game is that it can train students to get used to speaking Arabic, there is competition between students that makes learning interesting, reduces boredom and sleepiness in learning, while the disadvantage of this game is the use of Limited sentences, suitable use on certain themes, the use of this game is sometimes accompanied by loud voices from students that sometimes disturb other classes. تعلم اللغة ليس أمرا سهلا. لا تزال المشاكل المختلفة تنشأ بشكل متكرر ونادرا ما يتم حلها. مشكلة تعليم اللغة العربية تحتاج إلى اهتمام خاص. إن عدم النجاح في تعلم اللغة العربية في مختلف المراحل الدراسية يتأثر بشكل أساسي بعوامل كثيرة، منها أساليب واستراتيجيات التعليم الأقل نشاطا وإبداعا ومتعة، مما يجعل الطلاب في بعض الأحيان أقل حماسا للتعلم. يهدف هذا البحث إلى معرفة تطبيق لعبة التغمية اللغوية في تعليم مهارة الكلام بمدرسة المنير الابتدائية. ثانياً: معرفة مزايا وعيوب التغمية في تعلم مهارة الكلام بهذه المدرسة. يستخدم هذا البحث البحث النوعي مع تقنيات جمع البيانات باستخدام المقابلة والملاحظة. وأثبتت نتائج البحث أن تطبيق اللعبة اللغوية يتوافق مع خطة التدرس التي وضعها المعلم والتي تتكون من عدة مراحل تبدأ من المقدمة والأنشطة الرئيسية، والختام أنها تدرب الطلاب على التعود على التحدث باللغة العربية، وتوجد منافسة بين الطلاب مما يجعل التعلم ممتعاً، ويقلل من الملل والنعاس في التعلم، أما عيوب هذه اللعبة فهي استخدام جمل محدودة، واستخدامها مناسب. في بعض المواضيع، يكون استخدام هذه اللعبة مصحوبًا أحيانًا بأصوات عالية من الطلاب مما يؤدي في بعض الأحيان إلى إزعاج الفصول الأخرى.